Analysis of the alcohol drinking behavior and influencing factors among emerging adults and young adults: a cross-sectional study in Wuhan, China - Wanrong Lu; Jingdong Xu; Anne Winifred Taylor; Bridgette Maree Bewick; Zhen Fu; Nanjin Wu; Ling Qian; Ping Yin (BMC, 2019)
Abstract Background The relationship between alcohol use in adolescents and young adults and outcomes has not been widely researched in China. The aim of the current study was to understand the current status of drinking behavior of Chinese youth transitioning into adulthood. Methods The cross-sectional study included 1634 participants between 18 and 34 years of age. The participants were randomly chosen from 13 administrative districts in Wuhan, and invited to complete a questionnaire. Univariate analysis was performed to describe the demographic distribution of alcohol consumption and the association with drinking status. Stepwise Logistic regression analysis was undertaken analyzing the factors influencing the drinking behaviors. The data were weighted to the population in Wuhan and analyzed using SAS version 9.3. Results For our sample of emerging and young Chinese adults the prevalence of drinking alcohol was 45.84%. The non-drinkers predominated, accounting for 54.16% and light drinkers accounted for 42.94%, while moderate and heavy drinkers were in the minority (2.90%). The earlier the age of first alcohol drinking or the age of first being intoxicated, the greater the likelihood of being a moderate or heavy drinker. People with high emerging adulthood were more likely to have moderate or heavy drinking behaviors. The logistic regression analysis indicated that heavy drinkers were more likely to not be married and to be classified as high emerging adulthood. Conclusions Our findings suggested that the drinking pattern should be further evaluated over time to explore the ways in which social and cultural factors shape the drinking route of this age group. Effective drinking behavior prevention and interventions and appropriate guidance should be formulated to establish an appropriate attitude towards drinking alcohol and develop a drinking behavior which is conducive to physical and mental health between this particular demographic.